The Combination of hCG and GnRH Analog to Hasten Ovulation in Mares Does not Change Luteal Function and Pregnancy Outcome in Embryo Recipient Mares - Segabinazzi, Lorenzo G.T.M. [UNESP] (2021)
Equine practitioners often prescribe the combined use of hCG and GnRH to hasten ovulation due to presumed synergistic effects. Therefore, this study aimed to test whether the combination of hCG and deslorelin acetate to hasten ovulation in mares would show any effect in inducing ovulation more efficiently than when either drug is used by itself, and to verify whether this association would affect progesterone concentrations; corpus luteum (CL) diameter and blood flow; and pregnancy outcome in recipient mares after embryo transfer (ET). Seventeen mares had the ovulation hastened (≥35 mm follicle) as follow: Control, 1 mL of 0.9% NaCl solution; GnRH, 1 mg of deslorelin acetate; hCG, 1,500 IU of hCG; hCG+GnRH, 1mg of deslorelin acetate and 1,500 IU of hCG. CL diameter and blood flow, and serum progesterone concentrations were assessed between the day of ovulation induction and sixteen days after ovulation. In addition, data of 194 ET were retrospectively analyzed. Pregnancy rates at five days after ET and pregnancy loss up to 60 days of recipient mares with natural ovulation (Control, n=37), or with ovulation hastened with hCG (n=25), or deslorelin acetate (n=46), or the combination of these hormones (n=86), as described above, were assessed. The control group had a higher progesterone concentration on the day of ovulation than the GnRH group (P < .05). However, there were no differences in CL diameter and blood flow at any time point, as well as in progesterone concentration over time (P > .05). Pregnancy rates and pregnancy loss didn't differ between recipient mares treated or not with hormones. In conclusion, the combination of hCG and deslorelin acetate to hasten ovulation was not able to change luteal development, progesterone concentration, or pregnancy outcome in recipient mares after ET.